Influence of health status and loneliness on satisfaction with life, emotional dimensions, and distress in junior handball players - Miroljub Ivanović; Uglješa Ivanović (Exercise and Quality of Life)
This transversal study aimed to examine the contribution of predictor variables of the construct of health status (objective and subjective assessment of health) to the variability of the criteria satisfaction with life, emotional dimensions (positive affect, negative affect), and emotional factor of distress (depression, anxiety, and stress) in junior handball players. The pertinent sample consisted of 132 junior handball players in – Serbian First League. The average age of participants was 18.25 ± 0.90 years of age. The following measuring instruments were used: 1) the Depression, Anxiety, and Stress Scale – DASS-21, 2) De Jong Gierveld Loneliness Scale – DJGLS, 3) the Satisfaction with Life Scale‒ SWLS, and 4) The Positive and Negative Affect Schedule – PANAS showed satisfactory internal consistency. The conducted multiple regression analysis explained 51% of the proportion variance of the dependent variable satisfaction with life, positive and/or negative affectivity, and cognitive aspect of distress, where the only statistically significant negative predictors were loneliness and subjective assessment of health status. At the same time, when it comes to the assessment of loneliness in adolescents, these independent variables achieved significant interaction with the subjective assessment of health. This would mean that handball players, who subjectively assess their health as bad, and feel lonelier. On the other hand, the regression model did not confirm the role of the predictor variable objective assessment of health status and loneliness. This regression study has contributed to the existing literature and empirical data on the significance of the rarely explored relations between the constructs of health and well-being in the adolescent sports population. Theoretical contributions and practical implications for future research were also discussed.